2010
DOI: 10.1007/s11136-010-9703-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and quality of life survey among child survivors of the 2008 Sichuan earthquake

Abstract: More than one in five child survivors were identified as having PTSD or depression; HRQoL of these identified children were deeply compromised. Utilization of mental health services may significantly reduce the risk of developing PTSD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
6
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 38 publications
2
53
6
4
Order By: Relevance
“…These findings were generally consistent with those gained in previous reports (e.g., Ekşi et al, 2007;Fan et al, 2011;Liu et al, 2011), and suggest that youths who have experienced more traumatic events are more likely to develop PTSD. However, contrary to previous findings (e.g., Jia et al, 2010;Thienkrua et al, 2006;Trickey et al, 2012), no significant association was found between bereavement and PTSD in this study. According to Mercer, Ager, and Ruwanpura (2005) this discrepancy may be due to Tibetans' traditional beliefs, such as karma, which have a strong influence on everything in their lives including experiences of trauma.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings were generally consistent with those gained in previous reports (e.g., Ekşi et al, 2007;Fan et al, 2011;Liu et al, 2011), and suggest that youths who have experienced more traumatic events are more likely to develop PTSD. However, contrary to previous findings (e.g., Jia et al, 2010;Thienkrua et al, 2006;Trickey et al, 2012), no significant association was found between bereavement and PTSD in this study. According to Mercer, Ager, and Ruwanpura (2005) this discrepancy may be due to Tibetans' traditional beliefs, such as karma, which have a strong influence on everything in their lives including experiences of trauma.…”
Section: Discussioncontrasting
confidence: 99%
“…Each item is rated on a 5-point Likert scale ranging from 0 (none of the time) to 4 (most of the time), reflecting the frequency of occurrence of a particular symptom during the past month. The Chinese version of the UCLA PTSD Reaction Index was adapted using a back-translation procedure that has been validated and widely used in Chinese populations (e.g., Chen & Wu, 2006;Jia et al, 2010;Wu, Chen, Weng, & Wu, 2009). In the present study, participants were instructed to complete the index in relation to their experiences of the earthquake, and Cronbach's  was 0.88 for the PTSD symptom scale in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…PTS symptoms increased in the whole epicentre community likewise found elsewhere 15 months after an earthquake [16,17], but the rise was more pronounced in the children aged 6–10. In this group, prevalence of risk of psychiatric disorders (22.9%) reached levels predicted by the World Health Organization during the first year after disaster (23-24%) [49].…”
Section: Discussionmentioning
confidence: 83%
“…Focusing on data more relevant to the present study, between 12 and 18 months after natural disasters Wang et al [12] report that data from preschool children community samples are lacking, while for school age children and early adolescents self-reported prevalence of PTS and depression symptoms ranges from, respectively, 11.2% and 11.3% at 12 months [16], to 12.4% and 13.9% at 15 months [17], to 95% and 76% at 18 months after an earthquake [14]. Prevalence tend to be lower when data are collected through a psychiatric interview: according to DSM-IV criteria [18], PTSD prevalence is found 2.1%-4.7% 18 months after floods [19,20], while depression prevalence is found 5.4% 18–20 months after an earthquake [15].…”
Section: Introductionmentioning
confidence: 99%
“…A report from Sichuan, China in the aftermath of 2008 massive earthquake indicates that one in five child survivors were identified as having post traumatic stress disorder or depression and their health related quality of life were deeply compromised. 5 Plight of individuals specially children who have lost near and dear ones is understandable. However, treatment of physical injuries and physical rehabilitation almost completely over shadows the psychological stress people go through in situation like this.…”
mentioning
confidence: 99%